Primer composition
The primer composition, featuring a silicone surfactant, film-forming resin, and volatile organic solvent, addresses the issue of slipping curable sealants in joint formation by enhancing adhesion and preventing slipping, resulting in stable and defect-free joints.
Patent Information
- Application Number
- JP2023170076
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Conventional curable sealants used in joint formation tend to slip and slide off due to their own weight, leading to defects in the joint formation process, even when silicone surfactants are incorporated to prevent slipping.
A primer composition is developed that incorporates a silicone surfactant with a film-forming resin and a volatile organic solvent, which enhances the slip prevention properties by forming a primer layer that allows the silicone surfactant to migrate to the surface, improving adhesion and preventing slipping of the curable sealant.
The primer composition effectively prevents slipping of the curable sealant, ensuring a stable and defect-free joint formation process, as demonstrated by slip test results showing minimal to no slipping across various examples.
Abstract
Description
[Technical field]
[0001] The present invention relates to a primer composition used when forming joints in buildings, structures, etc., and to a primer composition that can effectively prevent the slip phenomenon of a curable sealant used when forming the joints. [Background technology]
[0002] Conventionally, for the purpose of waterproofing, etc., a hardening sealant has been filled into the gaps between exterior wall materials to form joints. The hardening sealant is in a paste form when filled, and then gradually hardens to become an elastic body, completing the joint. However, at the stage of changing from a paste form to an elastic body, the hardening sealant slips under its own weight and slides down, resulting in defects in the joint area where no elastic body exists.
[0003] For this reason, a silicone surfactant is added to the curable sealant to prevent slippage (Patent Document 1). However, there is still a disappointment that slippage cannot be sufficiently prevented.
[0004] [Patent Document 1] JP 2000-204348 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a primer composition for use in forming joints which is less susceptible to slippage than when a curable sealant contains a silicone surfactant. [Means for solving the problem]
[0006] The present inventors have been conducting research into the formation of joints that are less susceptible to slippage, and have discovered that a primer composition containing a volatile organic solvent and a silicone surfactant exhibits more remarkable slip prevention than a curable sealant. The present invention is based on this finding. That is, the present invention relates to a primer composition containing a film-forming resin, a silicone surfactant having a hydrophobic group consisting of an organopolysiloxane group and a hydrophilic group containing a group selected from the group consisting of a polyether group, a hydroxyl group, a mercapto group, and an amino group, and a volatile organic solvent.
[0007] The film-forming resin used in the present invention may be any known resin that can form a film to be a primer layer. For example, acrylic resin or urethane resin can be used. In particular, it is preferable to use a curable resin such as a curable acrylic resin or a curable urethane resin as the film-forming resin. This is because the primer layer obtained by curing the curable resin has high strength and excellent weather resistance. The curable acrylic resin is preferably an acrylic resin having a hydrolyzable silyl group at the end and / or side chain of the main chain made of an acrylic skeleton (hereinafter referred to as "acrylic silicone resin"). The hydrolyzable silyl group of the acrylic silicone resin is bonded and cured by moisture in the air. In addition, the curable urethane resin is preferably a polyisocyanate compound having mainly two or more isocyanate groups. The curable urethane resin is also cured by bonding the NCO group in the molecule due to moisture in the air.
[0008] The silicone surfactant used in the present invention has a hydrophobic group consisting of an organopolysiloxane group and a hydrophilic group containing a group selected from the group consisting of a polyether group, a hydroxyl group, a mercapto group, and an amino group. That is, the main skeleton is a siloxane bond consisting of alternately bonded Si (silicon) and O (oxygen), and hydrophilic groups selected from the group consisting of a polyether group, a hydroxyl group, a mercapto group, and an amino group are introduced into the main chain, side chain, or end. Such silicone surfactants are commercially available as amino-modified silicone oil, mercapto-modified silicone oil, polyether-modified polydimethylsiloxane having a hydroxyl group, or polyether-modified polydimethylsiloxane having an acrylic group.
[0009] The volatile organic solvent used in the present invention may be any conventionally known organic solvent that volatilizes at room temperature. Specifically, ethyl acetate, propyl acetate, butyl acetate, or the like is used. When a primer layer is formed using a primer composition containing a volatile organic solvent, a film is formed by the film-forming resin and the volatile organic solvent volatilizes from the surface, and it is considered that the silicone surfactant is easily transferred to the surface of the primer layer, and the slip prevention effect is easily exhibited. The content of the volatile organic solvent in the primer composition is preferably 50 to 95% by mass, more preferably 60 to 90% by mass, and most preferably 65 to 85% by mass.
[0010] The silicone surfactant used in the present invention is preferably blended in an amount of 0.01 to 5 parts by mass per 100 parts by mass of the film-forming resin. The volatile organic solvent is preferably blended in an amount of 100 to 800 parts by mass per 100 parts by mass of the film-forming resin. In addition, when a curable resin is used as the film-forming resin, it is preferable that a silane coupling agent or a catalyst is contained in the primer composition. For example, when an acrylic silicone resin is used, it is preferable to contain a silane coupling agent having a hydrolyzable silyl group and a reactive functional group selected from the group consisting of an amino group, an epoxy group, and a vinyl group. It is preferable to contain 5 to 200 parts by mass of the silane coupling agent per 100 parts by mass of the curable resin. Furthermore, it is preferable to contain a curing catalyst. This makes it easier for the acrylic silicone resin to cure. In addition, when a curable urethane resin is used, it is preferable to contain a silane coupling agent or a curing catalyst. In addition, even when the film-forming resin is a non-curable resin, it is preferable to contain a silane coupling agent or a curing catalyst.
[0011] The primer composition according to the present invention is applied to the surface of an adherend in order to improve the adhesion between the adherend and the adhesive when filling the adherend with a sealant or applying an adhesive. A specific method of use is to use it when forming a joint. For example, a method can be mentioned in which the primer composition according to the present invention is applied to a joint wall, a film is formed with a film-forming resin and a volatile organic solvent is volatilized to form a primer layer having a thickness of 1 to 50 μm, and then a curable sealant is filled on the primer layer to form a joint. The joint wall is generally U-shaped. The primer composition is applied to the surface of such a joint wall. The application amount is 2 to 500 g / m. 2The thickness of the primer layer is about 1 to 50 μm. After that, the volatile organic solvent in the primer composition evaporates, and a film is formed by the film-forming resin, which becomes a primer layer. The thickness of the primer layer is about 1 to 50 μm. It is considered that the silicone surfactant in the primer composition migrates to the surface of the primer layer as the volatile organic solvent evaporates. The presence of this silicone surfactant prevents the slippage of the curable sealant filled on the primer layer.
[0012] As the curable sealant filled on the primer layer, a conventionally known sealant is used. Specifically, modified silicone-based sealants mainly made of modified silicone resins and polyurethane-based sealants mainly made of urethane resins are used. Such curable sealants may contain various conventionally known additives. For example, fillers, diluents, silane coupling agents, catalysts, dehydrating agents, colorants such as titanium oxide or carbon black, photocurable resins (acryloyl group-containing resins, methacryloyl group-containing resins, etc.), drying oils, semi-drying oils (tung oil, castor oil, dehydrated castor oil, linseed oil, etc.), weather resistance agents, ultraviolet absorbers, anti-aging agents (hindered amine compounds, benzotriazole compounds, triazine compounds, hindered phenol compounds, etc.), etc. may be contained. If a silicone surfactant is contained in the curable sealant, slippage can be more effectively prevented.
[0013] The primer layer and the curable sealant are preferably made of the same or similar resins. This is because the adhesion between the primer layer and the curable sealant is improved. For example, when the resin constituting the primer layer is an acrylic silicone resin, it is preferable to use a modified silicone-based sealant mainly made of modified silicone resin as the curable sealant. Also, when the resin constituting the primer layer is made of a polyisocyanate compound having two or more isocyanate groups, it is preferable to use a polyurethane-based sealant mainly made of urethane resin as the curable sealant. However, the primer layer and the curable sealant may be different types. For example, even when an acrylic silicone resin is used as the resin constituting the primer layer, the adhesion with the polyurethane-based sealant is improved if a silane coupling agent having a reactive functional group selected from the group consisting of an amino group, an epoxy group, and a vinyl group is present in the primer layer. Effect of the Invention
[0014] When a primer layer is formed using the primer composition according to the present invention and then a sealant is filled in to form a joint, it is possible to prevent the sealant from slipping. EXAMPLES
[0015] Example 1 A primer composition having the following composition was obtained. Acrylic silicone resin 100 parts by weight (Kaneka Corporation "Kaneka Gemrack YP1915B") (*1) Silane coupling agent having an epoxy group: 2 parts by weight ("KBM403" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having an amino group: 1 part by weight ("KBM603" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having a vinyl group: 1 part by weight ("KBM1003" manufactured by Shin-Etsu Chemical Co., Ltd.) Organotin catalyst 0.1 parts by mass ("Neostan U-130" manufactured by Nitto Kasei Co., Ltd.) Polyether-modified polydimethylsiloxane having hydroxyl groups: 1 part by mass (BYK-377 manufactured by BYK Japan Co., Ltd.) Propyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 50 parts by weight (*1) Kaneka Corporation's "Kaneka Gemlac YP1915B" is a compound consisting of 40 parts by mass of an acrylic silicone resin having a hydrolyzable silyl group at the end of the main chain, 55 parts by mass of butyl acetate, and 5 parts by mass of other compounds.
[0016] Example 2 A primer composition was obtained in the same manner as in Example 1, except that the polyether-modified polydimethylsiloxane having a hydroxyl group (manufactured by BYK-377 in Japan) was replaced with a polyether-modified polydimethylsiloxane having an acrylic group (manufactured by BYK-UV3500 in Japan).
[0017] Example 3 Hydroxyl-containing polyether-modified polydimethylsiloxane (BYK-377, manufactured by BYK Japan Co., Ltd.) was mixed with amino-modified silicone oil (DOWSIL TM A primer composition was obtained in the same manner as in Example 1, except that the solvent used was changed to "FZ-3789".
[0018] Example 4 A primer composition was obtained with the same formulation as in Example 1, except that the polyether-modified polydimethylsiloxane having a hydroxyl group (BYK-377 manufactured by BYK Japan K.K.) was replaced with a polyether-modified silicone oil (KF-945 manufactured by Shin-Etsu Chemical Co., Ltd.).
[0019] Example 5 A primer composition was obtained in the same manner as in Example 1, except that the polyether-modified polydimethylsiloxane having a hydroxyl group (manufactured by BYK Japan K.K., "BYK-377") was replaced with a mercapto-modified silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd., "KF-2001").
[0020] Example 6 A primer composition having the following composition was obtained. Acrylic silicone resin 100 parts by weight (Kaneka Corporation "Kaneka Gemrack YP1915B") (*1) Silane coupling agent having an epoxy group: 5 parts by weight ("KBM403" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having an amino group: 2 parts by weight ("KBM903" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having an amino group: 1 part by weight (Evonik "Dynasylan1124") Silane coupling agent having a vinyl group: 1 part by weight ("KBM1003" manufactured by Shin-Etsu Chemical Co., Ltd.) Organotin catalyst 0.2 parts by mass (Kaneka Corporation "BT453Z") Polyether-modified polydimethylsiloxane having hydroxyl groups: 0.5 parts by mass (BYK-377 manufactured by BYK Japan Co., Ltd.) Amino modified silicone oil 0.5 parts by mass (Dow Toray Industries, Inc. "DOWSIL TM FZ-3789" Ethyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 25 parts by mass Propyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 50 parts by weight (*1) Same as in Example 1.
[0021] Example 7 A primer composition having the following composition was obtained. Acrylic silicone resin 100 parts by weight (Kaneka Corporation "Kaneka Gemrack YP1915B") (*1) Silane coupling agent having an epoxy group: 2 parts by weight ("KBM403" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having an amino group: 2 parts by weight ("KBM903" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having a vinyl group: 2 parts by weight ("KBM1003" manufactured by Shin-Etsu Chemical Co., Ltd.) Organotin catalyst 0.2 parts by mass ("Neostan S-1" manufactured by Nitto Kasei Co., Ltd.) Amino modified silicone oil 0.02 parts by mass (Dow Toray Industries, Inc. "DOWSIL TM FZ-3789" Ethyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 25 parts by mass Propyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 25 parts by mass (*1) Same as in Example 1.
[0022] Example 8 Amino-modified silicone oil (Dow Toray Co., Ltd. "DOWSIL TM A primer composition was obtained with the same formulation as in Example 7, except that the blending amount of "FZ-3789" was changed to 5 parts by mass.
[0023] Example 9 The catalyst was not an organotin catalyst ("Neostan S-1" manufactured by Nitto Chemical Industry Co., Ltd.) and it was not an amino-modified silicone oil ("DOWSIL" manufactured by Dow Toray Co., Ltd.). TM A primer composition was obtained with the same formulation as in Example 7, except that the blending amount of "FZ-3789" was changed to 0.05 parts by mass.
[0024] Example 10 The amount of the silane coupling agent having an epoxy group ("KBM403" manufactured by Shin-Etsu Chemical Co., Ltd.) was changed to 100 parts by mass, without using a silane coupling agent having an amino group ("KBM903" manufactured by Shin-Etsu Chemical Co., Ltd.) and a silane coupling agent having a vinyl group ("KBM1003" manufactured by Shin-Etsu Chemical Co., Ltd.), and amino-modified silicone oil ("DOWSIL" manufactured by Dow-Toray Co., Ltd.) was added. TM A primer composition was obtained with the same formulation as in Example 7, except that the blending amount of "FZ-3789" was changed to 0.05 parts by mass.
[0025] Example 11 The amount of the silane coupling agent having an amino group ("KBM903" manufactured by Shin-Etsu Chemical Co., Ltd.) was changed to 100 parts by mass, without using a silane coupling agent having an epoxy group ("KBM403" manufactured by Shin-Etsu Chemical Co., Ltd.) or a silane coupling agent having a vinyl group ("KBM1003" manufactured by Shin-Etsu Chemical Co., Ltd.), and amino-modified silicone oil ("DOWSIL" manufactured by Dow-Toray Co., Ltd.) was added. TM A primer composition was obtained with the same formulation as in Example 7, except that the blending amount of "FZ-3789" was changed to 0.05 parts by mass.
[0026] Example 12 The amount of the silane coupling agent having a vinyl group ("KBM1003" manufactured by Shin-Etsu Chemical Co., Ltd.) was changed to 100 parts by mass, without using a silane coupling agent having an epoxy group ("KBM403" manufactured by Shin-Etsu Chemical Co., Ltd.) or an amino group ("KBM903" manufactured by Shin-Etsu Chemical Co., Ltd.), and an amino-modified silicone oil ("DOWSIL" manufactured by Dow-Toray Co., Ltd.) was added. TM A primer composition was obtained with the same formulation as in Example 7, except that the blending amount of "FZ-3789" was changed to 0.05 parts by mass.
[0027] Example 13 A primer composition having the following composition was obtained. Acrylic silicone resin 100 parts by weight (Kaneka Corporation "Kaneka Gemrack YP1915B") (*1) Silane coupling agent having an epoxy group: 10 parts by weight ("KBM403" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having an epoxy group: 1 part by weight ("KBM402" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having an amino group: 2 parts by weight ("KBM903" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent having an amino group: 0.5 parts by mass (Evonik "Dynasylan1124") Organotin catalyst 0.2 parts by mass ("Neostan S-1" manufactured by Nitto Kasei Co., Ltd.) Amino modified silicone oil 0.1 parts by mass (Dow Toray Industries, Inc. "DOWSIL TM FZ-3789" Ethyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 25 parts by mass Propyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 25 parts by mass (*1) Same as in Example 1.
[0028] Example 14 A primer composition was obtained with the same formulation as in Example 13, except that a silane coupling agent having an epoxy group ("KBM303" manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of the silane coupling agent having an epoxy group ("KBM402" manufactured by Shin-Etsu Chemical Co., Ltd.).
[0029] Example 15 A primer composition was obtained with the same formulation as in Example 13, except that a silane coupling agent having an amino group ("KBM602" manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of a silane coupling agent having an epoxy group ("KBM402" manufactured by Shin-Etsu Chemical Co., Ltd.).
[0030] Example 16 A primer composition was obtained with the same formulation as in Example 13, except that a silane coupling agent having a vinyl group ("KBM1003" manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of a silane coupling agent having an epoxy group ("KBM402" manufactured by Shin-Etsu Chemical Co., Ltd.).
[0031] Example 17 A primer composition was obtained with the same formulation as in Example 13, except that a silane coupling agent having an alkyl group ("KBM3103C" manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of a silane coupling agent having an epoxy group ("KBM402" manufactured by Shin-Etsu Chemical Co., Ltd.).
[0032] Example 18 A primer composition having the following composition was obtained. Polyisocyanate compound 670 parts by mass (Mitsui Chemicals "Takenate D103M-2") Acrylic resin 100 parts by weight (Dow Toray Industries, Inc. "Paraloid A21") Silane coupling agent 90 parts by weight ("KBM803" manufactured by Shin-Etsu Chemical Co., Ltd.) p-Toluenesulfonyl isocyanate (dehydrating agent) 5 parts by mass Polyether-modified polydimethylsiloxane having hydroxyl groups: 1 part by mass (BYK-377 manufactured by BYK Japan Co., Ltd.) Ethyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 670 parts by mass Butyl acetate (manufactured by Daihachi Chemical Industry Co., Ltd.) 520 parts by mass
[0033] Comparative Example 1 A primer composition was obtained with the same formulation as in Example 1, except that the hydroxyl-containing polyether-modified polydimethylsiloxane was not blended.
[0034] Comparative Example 2 Hydroxyl-containing polyether-modified polydimethylsiloxane (BYK-377, manufactured by BYK Japan Co., Ltd.) and amino-modified silicone oil (DOWSIL TM A primer composition was obtained in the same manner as in Example 6, except that "FZ-3789" was not blended.
[0035] Comparative Example 3 A primer composition was obtained in the same manner as in Example 18, except that no hydroxyl-containing polyether-modified polydimethylsiloxane (BYK-377 manufactured by BYK Japan Co., Ltd.) was added.
[0036] [Slip test 1] At a temperature of 23° C. and a humidity of 50%, the primer composition according to Example 1 was applied to both inner surfaces of a U-shaped aluminum channel having a width of 20 mm, a depth of 20 mm, and a length of 100 mm at about 40 g / m 2 After the primer composition was applied in an amount of 0.01 mm, a masking tape was applied to the bottom surface. The primer composition was then dried to form a primer layer having a thickness of about 5 to 20 μm. The curable sealant A shown below was applied to both inner surfaces on which the primer layer was formed, and filled in the grooves of the U-shaped aluminum channel so as to fill them. Since masking tape was applied to the bottom surface of the U-shaped aluminum channel, the primer layer and the curable sealant A were bonded to both inner surfaces. After that, the aluminum channel was vertically stood up in an environment of 40° C. and left for 24 hours. After 24 hours, the slip length of the curable sealant A was 0 mm, and the results of the slip test were good. The criteria for the slip test were that a slip length of 0 mm was evaluated as "good", a slip length of less than 5 mm was evaluated as "good", and a slip length of 5 mm or more was evaluated as "poor".
[0037] The curable sealant A was prepared by uniformly mixing 100 parts by mass of a sealant base A having the composition shown below and 8.0 parts by mass of a sealant curing agent A having the composition shown below. (Sealant Base A) Modified silicone polymer 100 parts by weight (AGC Corporation "EXCESTAR S2730C") Modified silicone polymer 10 parts by weight (Kaneka Corporation "Sylil SAT145") Diisononyl phthalate (manufactured by Daihachi Chemical Industry Co., Ltd.) 10 parts by mass Plasticizer having an alicyclic epoxy group 50 parts by weight ("Sanso Cizer E-PS" manufactured by New Japan Chemical Co., Ltd.) Polyether-modified polydimethylsiloxane having hydroxyl groups: 1 part by mass (BYK-377 manufactured by BYK Japan Co., Ltd.) Plastic balloon 6 parts by weight (Matsumoto MFL100MCA manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) Silicone oil-treated hydrophobic silica 1 part by weight (Aerosil RY200S, manufactured by Nippon Aerosil Co., Ltd.) Ground calcium carbonate 30 parts by weight ("Super S" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 100 parts by mass ("Calcine 200M" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 40 parts by mass ("Calcine N-350" manufactured by Maruo Calcium Co., Ltd.) Isoparaffin 10 parts by weight (Idemitsu Kosan Co., Ltd. "Merveille 30") (Sealant hardener A) 1,2-Cyclohexanedicarboxylic acid diisononyl ester 12 parts by mass ("Hexamol DINCH" manufactured by BASF Japan Ltd.) Inorganic tin catalyst 12 parts by mass ("Neostan U-28" manufactured by Nitto Kasei Co., Ltd.) Amine catalyst (dodecylamine) 3 parts by mass Ground calcium carbonate 25 parts by weight ("Super S" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 20 parts by mass ("Calcine N-350" manufactured by Maruo Calcium Co., Ltd.) Isoparaffin 8 parts by weight (Idemitsu Kosan Co., Ltd. "Merveille 30")
[0038] [Slip tests 2-6] Slip tests 2 to 5 were performed in the same manner as slip test 1, except that the primer compositions according to Examples 2 to 5 were used instead of the primer composition according to Example 1. As a result, the slip length of the curable sealant A was 0 mm in all cases, and the results of the slip test were good. In addition, slip test 6 was performed in the same manner as slip test 1, except that the primer composition according to Comparative Example 1 was used instead of the primer composition according to Example 1. As a result, the slip length of the curable sealant A was 10 mm or more, and the results of the slip test were poor.
[0039] [Slip test 7] Slip test 7 was carried out in the same manner as slip test 1, except that the primer composition of Example 6 was used instead of the primer composition of Example 1, and the curable sealant B shown below was used instead of the curable sealant A. As a result, the slip length of the curable sealant B was 0 mm, and the result of the slip test was good. Curable sealant B is a uniform mixture of 100 parts by mass of sealant base B and 8.0 parts by mass of sealant hardener A. Here, sealant base B has the same formulation as sealant base A, except that it does not contain polyether-modified polydimethylsiloxane having hydroxyl groups (BYK-377 manufactured by BYK Japan Co., Ltd.).
[0040] [Slip test 8] Slip test 7 was carried out in the same manner as in slip test 7, except that curable sealant C described below was used instead of curable sealant B. As a result, the slip length of curable sealant C was 0 mm, and the results of the slip test were good. The curable sealant C is prepared by uniformly mixing 100 parts by mass of sealant base C and 8.0 parts by mass of sealant curing agent A. Here, the sealant base C has the following formulation. (Sealant Base C) Modified silicone polymer 100 parts by weight (AGC Corporation "EXCESTAR S2730C") Modified silicone polymer 5 parts by weight (Kaneka Corporation "Sylil SAT145") Polyether polyol 70 parts by weight (AGC Corporation "Preminol S4012") Plasticizer having an alicyclic epoxy group 10 parts by weight (Daicel Corporation "Celloxide 2021P") Plastic balloon 3 parts by weight (Matsumoto MFL100MCA manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) Plastic balloon 3 parts by weight (Matsumoto MFL110CAL manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) Silicone oil-treated hydrophobic silica 1 part by weight (Aerosil RY200S, manufactured by Nippon Aerosil Co., Ltd.) Ground calcium carbonate 50 parts by mass ("Super S" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 40 parts by mass ("Calcine 200M" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 60 parts by mass ("Calcine N-350" manufactured by Maruo Calcium Co., Ltd.) Isoparaffin 10 parts by weight (Idemitsu Kosan Co., Ltd. "Merveille 30")
[0041] [Slip test 9] Slip test 9 was conducted in the same manner as slip test 7, except that curable sealant D shown below was used instead of curable sealant B. As a result, the slip length of curable sealant D was 0 mm, and the results of the slip test were good. The curable sealant D is prepared by uniformly mixing 100 parts by mass of sealant base D and 8.0 parts by mass of sealant curing agent A. Here, sealant base D has the following formulation. (Sealant Base D) Modified silicone polymer 100 parts by weight (AGC Corporation "EXCESTAR S2730C") Modified silicone polymer 10 parts by weight (Kaneka Corporation "Sylil SAT145") Polyether polyol 30 parts by mass (AGC Corporation "Preminol S3011") Plasticizer having an alicyclic epoxy group: 25 parts by weight ("Rikaresin EX-68" manufactured by New Japan Chemical Co., Ltd.) Plastic balloon 3 parts by weight (Matsumoto MFL100MCA manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) Plastic balloon 3 parts by weight (Matsumoto MFL110CAL manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) Kaolin 5 parts by weight ("Hydrite N" manufactured by Imerys Minerals Japan Co., Ltd.) Ground calcium carbonate 70 parts by weight ("Super S" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 60 parts by mass ("Calcine 200M" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 40 parts by mass ("Calcine N-350" manufactured by Maruo Calcium Co., Ltd.) Isoparaffin 15 parts by weight (Idemitsu Kosan Co., Ltd. "Merveille 30")
[0042] [Slip test 10] Slip test 10 was conducted in the same manner as slip test 7, except that curable sealant E shown below was used instead of curable sealant B. As a result, the slip length of curable sealant E was 0 mm, and the results of the slip test were good. The curable sealant E is a homogeneous mixture of 100 parts by mass of sealant base E and 8.0 parts by mass of sealant hardener A. Here, the sealant base E has the following formulation. (Sealant Base E) Modified silicone polymer 100 parts by weight (AGC Corporation "EXCESTAR S2730C") Modified silicone polymer 40 parts by weight (Kaneka Corporation "Sylil SAT145") Acrylic oligomer plasticizer 15 parts by weight (“UP-1110” manufactured by Toagosei Co., Ltd.) Diisononyl phthalate (manufactured by Daihachi Chemical Industry Co., Ltd.) 10 parts by mass Plasticizer having an alicyclic epoxy group 10 parts by weight ("Sanso Cizer E-PS" manufactured by New Japan Chemical Co., Ltd.) Plasticizer with alicyclic epoxy group: 5 parts by weight (Daicel Corporation "Celloxide 2021P") Plastic balloon 6 parts by weight (Matsumoto MFL110CAL manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) Kaolin 5 parts by weight ("Hydrite N" manufactured by Imerys Minerals Japan Co., Ltd.) Ground calcium carbonate 70 parts by weight ("Super S" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 40 parts by mass ("Calcine 200M" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 50 parts by mass ("Calcine N-350" manufactured by Maruo Calcium Co., Ltd.) Isoparaffin 10 parts by weight (Idemitsu Kosan Co., Ltd. "Merveille 30") Polyethylene fiber 1 part by weight ("Chemibest FDSS-5" manufactured by Mitsui Chemicals Fine Co., Ltd.)
[0043] [Slip test 11] Slip test 11 was conducted in the same manner as slip test 7, except that curable sealant F shown below was used instead of curable sealant B. As a result, the slip length of curable sealant F was 0 mm, and the results of the slip test were good. The curable sealant F is prepared by uniformly mixing 100 parts by mass of sealant base F and 8.0 parts by mass of sealant curing agent A. Here, the sealant base F has the following formulation. (Sealant Base F) Modified silicone polymer 100 parts by weight (AGC Corporation "EXCESTAR S2730C") Polyether polyol 60 parts by weight (AGC Corporation "Preminol S3011") Plasticizer having an alicyclic epoxy group: 15 parts by weight ("Rikaresin EX-68" manufactured by New Japan Chemical Co., Ltd.) Plastic balloon 4 parts by weight (Matsumoto MFL110CAL manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) Glass balloon 2 parts by weight (3M Japan Ltd. "Glass Bubbles S22") Ground calcium carbonate 60 parts by weight ("Super S" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 80 parts by mass ("Calcine 200M" manufactured by Maruo Calcium Co., Ltd.) Light calcium carbonate 30 parts by mass ("Calcine N-350" manufactured by Maruo Calcium Co., Ltd.) Isoparaffin 10 parts by weight (Idemitsu Kosan Co., Ltd. "Merveille 30") Polyethylene fiber 0.5 parts by weight ("Chemibest FDSS-5" manufactured by Mitsui Chemicals Fine Co., Ltd.)
[0044] [Slip test 12~16] Slip test 12 was performed in the same manner as slip test 7, except that the primer composition of Comparative Example 2 was used instead of the primer composition of Example 6. Similarly, slip tests 13 to 16 were performed in the same manner as slip tests 8 to 11, except that the primer composition of Comparative Example 2 was used instead of the primer composition of Example 6. As a result, the slip lengths of the curable sealant materials B to F were all 10 mm or more, and the results of the slip tests were poor.
[0045] [Slip test 17] Slip test 17 was carried out in the same manner as slip test 1, except that the primer composition of Example 7 was used instead of the primer composition of Example 1, and a curable sealant [modified silicone sealant, "Bond MS Seal" manufactured by Konishi Co., Ltd. (mixed mass ratio of base:curing agent = 100:8.0)] (hereinafter simply referred to as "MS Seal") was used instead of the curable sealant A. As a result, the slip length of the MS Seal was 0 mm, and the result of the slip test was good.
[0046] [Slip Test 18~29] Slip tests 18 to 28 were performed in the same manner as slip test 17, except that the primer compositions according to Examples 8 to 18 were used instead of the primer composition according to Example 7. As a result, the slip length of the MS seal was 0 mm, and the results of the slip test were good. In addition, slip test 29 was performed in the same manner as slip test 17, except that the primer composition according to Comparative Example 3 was used instead of the primer composition according to Example 7. As a result, the slip length of the MS seal was 10 mm or more, and the results of the slip test were poor.
[0047] From the above results of the slip test, it can be seen that the use of the primer compositions of Examples 1 to 18, which contain a silicone-based surfactant, can prevent the slip phenomenon of the applied curable sealant, compared to the use of the primer compositions of Comparative Examples 1 to 3, which do not contain a silicone-based surfactant.
[0048] [Adhesion test 1] The primer composition according to Example 13 was applied at a rate of about 40 g / m to a painted aluminum sash ("YA-4N" manufactured by YKK AP Co., Ltd.). 2 The primer composition was applied with a brush in an amount of 1000 ml, the primer composition was dried, a primer layer was formed, and then MS Seal was applied. Adhesion Test 1 was performed according to the test method in accordance with "Standard Specifications for Building Construction and Commentary JASS8 Waterproofing Work (2022 Edition) 2.3.2 f(1)". The result of Adhesion Test 1 was "○". This Adhesion Test 1 evaluates the adhesion between the cured MS Seal and the primer layer of the joint, since even if the slip phenomenon before hardening of the MS Seal is prevented, if the adhesion to the joint after hardening is insufficient, it is considered to be unsuitable as a sealant. The judgment criteria for the adhesion test were that if the MS Seal suffered cohesive failure or thin layer cohesive failure, it was evaluated as "○", and if the MS Seal suffered interfacial peeling, it was evaluated as "×".
[0049] [Adhesion tests 2-5] Adhesion Tests 2 to 5 were performed in the same manner as Adhesion Test 1, except that the primer compositions according to Examples 14 to 17 were applied by brush instead of the primer composition according to Example 13. The results of Adhesion Tests 2 to 5 were all "◯".
[0050] [Adhesion test 6] Adhesion Test 6 was carried out in the same manner as Adhesion Test 1, except that a curable sealant [polyurethane sealant, "Bond View Seal 6909" manufactured by Konishi Co., Ltd. (mixed mass ratio of base:curing agent = 100:450)] (hereinafter simply referred to as "View Seal") was used instead of MS Seal. The result of Adhesion Test 6 was judged as "x". When a slip test was carried out in addition to Adhesion Test 6, the slip length was 0 mm, and the result was good.
[0051] [Adhesion tests 7-10] Adhesion tests 7 to 10 were performed in the same manner as adhesion test 6, except that the primer compositions according to Examples 14 to 17 were applied by brush instead of the primer composition according to Example 13. The results of adhesion tests 7, 8, and 10 were all judged as "x". On the other hand, the result of adhesion test 9 was judged as "○". This is considered to be because the primer composition according to Example 16 contains a silane coupling agent having a vinyl group ("KBM1003" manufactured by Shin-Etsu Chemical Co., Ltd.), which improves adhesion to polyurethane sealants. In addition to adhesion tests 7 to 10, slip tests were performed, and all slip lengths were 0 mm, showing good results.
Claims
1. Film-forming resins, A silicone surfactant having a hydrophobic group consisting of an organopolysiloxane group and a hydrophilic group containing a group selected from the group consisting of a polyether group, a hydroxyl group, a mercapto group, and an amino group; and Volatile organic solvents A primer composition comprising:
2. 2. The primer composition according to claim 1, which contains 0.01 to 5 parts by weight of a silicone surfactant and 100 to 800 parts by weight of a volatile organic solvent per 100 parts by weight of the film-forming resin.
3. 2. The primer composition of claim 1, wherein the film-forming resin is a curable resin.
4. 4. The primer composition according to claim 3, wherein the curable resin is an acrylic resin having a hydrolyzable silyl group at the end of the main chain and / or at a side chain of the acrylic skeleton.
5. 5. The primer composition according to claim 4, further comprising a silane coupling agent having a hydrolyzable silyl group and a reactive functional group selected from the group consisting of an amino group, an epoxy group and a vinyl group.
6. The primer composition according to claim 5, comprising 5 to 200 parts by mass of a silane coupling agent per 100 parts by mass of the curable resin.
7. 4. The primer composition according to claim 3, wherein the curable resin is a polyisocyanate compound having two or more isocyanate groups.
8. A method for forming a joint, comprising the steps of: applying the primer composition according to claim 1 to a joint wall; forming a film with a film-forming resin and simultaneously volatilizing the volatile organic solvent; forming a primer layer having a thickness of 1 to 50 μm; and then filling the primer layer with a curable sealant.